2019
DOI: 10.7554/elife.48167
|View full text |Cite
|
Sign up to set email alerts
|

Golgi localized β1-adrenergic receptors stimulate Golgi PI4P hydrolysis by PLCε to regulate cardiac hypertrophy

Abstract: Increased adrenergic tone resulting from cardiovascular stress leads to development of heart failure, in part, through chronic stimulation of β1 adrenergic receptors (βARs) on cardiac myocytes. Blocking these receptors is part of the basis for β-blocker therapy for heart failure. Recent data demonstrate that G protein-coupled receptors (GPCRs), including βARs, are activated intracellularly, although the biological significance is unclear. Here we investigated the functional role of Golgi βARs in rat cardiac my… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 36 publications
4
102
0
Order By: Relevance
“…A number of studies have also documented cAMP signaling from intracellular GPCRs that are located at intracellular membranes independently from receptor internalization ( Kumar et al, 2008 ; Suofu et al, 2017 ; Dahl et al, 2018 ; Nash et al, 2019 ). For example, studies show that a pre-existing β 1 -AR receptor pool that is not delivered from the cell surface resides at the Golgi, where it can be activated by endogenous ligands that enter the cell by facilitated transport via the organic cation transporter 3 ( Irannejad et al, 2017 ).…”
Section: Contribution To Compartmentalization Of Individual Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have also documented cAMP signaling from intracellular GPCRs that are located at intracellular membranes independently from receptor internalization ( Kumar et al, 2008 ; Suofu et al, 2017 ; Dahl et al, 2018 ; Nash et al, 2019 ). For example, studies show that a pre-existing β 1 -AR receptor pool that is not delivered from the cell surface resides at the Golgi, where it can be activated by endogenous ligands that enter the cell by facilitated transport via the organic cation transporter 3 ( Irannejad et al, 2017 ).…”
Section: Contribution To Compartmentalization Of Individual Pathmentioning
confidence: 99%
“…For example, studies show that a pre-existing β 1 -AR receptor pool that is not delivered from the cell surface resides at the Golgi, where it can be activated by endogenous ligands that enter the cell by facilitated transport via the organic cation transporter 3 ( Irannejad et al, 2017 ). Activation of this internal pool of receptors induces Epac-phospholipase C ε (PLC ε )–dependent phosphatidylinositol-4-phosphate (PI4P) hydrolysis in a process that has been linked to catecholamine-dependent cardiomyocyte hypertrophy ( Nash et al, 2019 ).…”
Section: Contribution To Compartmentalization Of Individual Pathmentioning
confidence: 99%
“…PLCε was recently reported to be activated at the Golgi, and not at the PM in cardiac cells, to hydrolyze phosphatidylinositol 4-phosphate [PI(4)P] (Malik et al, 2015; Nash et al, 2019; Zhang et al, 2013). Our optogenetic system, iLID-CAAX KRas , largely localizes to the PM but is also partially localized in the Golgi.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of Golgi β 1 AR triggers Golgi internal G s -mediated cAMP response contributing to overall cellular β 1 AR-mediated cAMP level changes ( Figure 1 I) ( Irannejad et al., 2017 ). This effect seems to be physiologically relevant since it is recently shown that blocking of Golgi β 1 AR inhibits norepinephrine-induced cardiac myocyte hypertrophy ( Nash et al., 2019 ).…”
Section: Er and Golgi Gpcrsmentioning
confidence: 98%